Modelos no domínio do tempo para o cálculo de tensões induzidas por descargas atmosféricas em programas de simulação de transitórios eletromagnéticos - Ósis Eduardo Silva Leal (2020)
Studies of lightning overvoltages in electrical systems are frequently performed in electromagnetic transient simulators. These platforms allow, through their vast and expansive library of components, a realistic representation of electrical systems with complex topology. However, the transmission line models available on such platforms do not include the effects of external electromagnetic fields in their formulation, which hinders their use of such models in the simulation of voltages induced by indirect lightning strikes. In order to perform this type of study, it is necessary to implement a dedicated line model that includes the effect of external fields and then to perform the interface of this model with the electromagnetic transient simulator. This process is problematic for reducing the efficiency of the simulation and introducing errors and numerical instability problems. In this thesis, two novel models are proposed for the calculation of lightning-induced voltages that allow the direct use of the frequency-dependent transmission line models already available in electromagnetic transient simulators. The first model, compatible with the JMarti transmission line model, also known as Fd-line, is developed in the modal domain. The second model, compatible with the Universal Line Model (ULM), is developed in the phase domain. The validity of the models is demonstrated through comparisons with results obtained with models available in the literature and experimental results. The computational efficiency of the proposed models and their sensitivity to segmentation and integration techniques are also investigated. The obtained results indicate that the proposed models can be used efficiently and consistently in the simulation of lightning-induced voltages on electromagnetic transient simulators.